Gonçalves Dias, o índio e a liberdade - Marques, Wilton José [UNESP] (My University, 2010)
This article presents a reading of the poem “O canto do guerreiro” written by Antonio Gonçalves Dias. The aim is to show the existence of a dialogue between the literary‘representation of the Brazilian‘indigenous and the concept of natural man, by Jean Jacques Rousseau. Going beyond a reading upon a romantic nationalism view, such dialogue makes explicit the poet’ conscience of his hole in Brazilian Romanticism and, at same time, gives a universal dimension to his poetic work.

O artigo faz uma leitura de “O canto do guerreiro”, de Antonio Gonçalves Dias. Essa leitura intenta mostrar a existência de um diálogo entre a representação literária do índio brasileiro e o conceito de homem natural de Jean Jacques Rousseau. Para além do viés nacionalista, tal diálogo explicita a consciência do poeta em relação ao seu papel no Romantismo brasileiro e, ao mesmo tempo, confere um traço universal à sua obra poética.
Gonçalves Dias, the indigenous and the liberty
Keywords: Gonçalves Dias; Indianism; “O canto do guerreiro”; Gonçalves Dias; Indianismo; Romantismo Brasileiro; Canto do guerreiro